2008
DOI: 10.1104/pp.107.111096
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Prospects for Engineering Insect-Resistant Plants  

Abstract: Insect-resistant crops have been one of the major successes of applying plant genetic engineering technology to agriculture; cotton (Gossypium hirsutum) resistant to lepidopteran larvae (caterpillars) and maize (Zea mays) resistant to both lepidopteran and coleopteran larvae (rootworms) have become widely used in global agriculture and have led to reductions in pesticide usage and lower production costs (Toenniessen et al., 2003;Brookes and Barfoot, 2005).The source of the insecticidal toxins produced in comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(100 citation statements)
references
References 51 publications
1
94
0
5
Order By: Relevance
“…This objective is pursued not only in the perspective of finding alternative genes for engineering new insect-resistant plants, which is highly needed (Gatehouse, 2008), but also to develop new bioinsecticides and effective delivery strategies, not exclusively based on the use of transgenic plants. This approach aiming at a sustainable exploitation of insect natural antagonism, obviously applies to a large variety of insect antagonists, which offer a virtually unlimited reservoir of new molecules with insecticide activity (Wethstone and Hammock, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This objective is pursued not only in the perspective of finding alternative genes for engineering new insect-resistant plants, which is highly needed (Gatehouse, 2008), but also to develop new bioinsecticides and effective delivery strategies, not exclusively based on the use of transgenic plants. This approach aiming at a sustainable exploitation of insect natural antagonism, obviously applies to a large variety of insect antagonists, which offer a virtually unlimited reservoir of new molecules with insecticide activity (Wethstone and Hammock, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An Update by Gatehouse (2008) in this issue highlights advances in transgenic approaches for creating insect-resistant crops. Enthusiasm for the use of plant proteinase inhibitors for crop protection has been tempered by the realization that insects have the capacity to synthesize, on demand, gut proteases that are insensitive to plant-derived inhibitors.…”
mentioning
confidence: 99%
“…By contrast, significant progress has been made in recent years towards the genetic transformation and in vitro regeneration of commercial banana and plantain varieties (Pérez Hernandez et al, 2006;Pommerrenig et al, 2006;Khanna et al, 2007), paving the way to the development of insectresistant transgenic banana lines. A number of recombinant proteins with pesticidal, antidigestive or antifeedant properties have been identified or devised over the years for the development of herbivorous pest-resistant crops by genetic transformation (Carlini and Grossi-de-Sá, 2002;Christou et al, 2006;Gatehouse, 2008;Zhu-Salzman et al, 2008). An engineered version of the rice cysteine protease inhibitor oryzacystatin I (OC-I) (Urwin et al, 1995) was shown, notably, to confer nematode resistance in transgenic banana lines genetically transformed with the corresponding transgene sequence (Atkinson et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%